2008
DOI: 10.1523/jneurosci.4178-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptome Database for Astrocytes, Neurons, and Oligodendrocytes: A New Resource for Understanding Brain Development and Function

Abstract: Understanding the cell-cell interactions that control CNS development and function has long been limited by the lack of methods to cleanly separate neural cell types. Here we describe methods for the prospective isolation and purification of astrocytes, neurons, and oligodendrocytes from developing and mature mouse forebrain. We used FACS (fluorescent-activated cell sorting) to isolate astrocytes from transgenic mice that express enhanced green fluorescent protein (EGFP) under the control of an S100␤ promoter.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

204
3,204
12
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 2,801 publications
(3,427 citation statements)
references
References 70 publications
204
3,204
12
7
Order By: Relevance
“…As expected, a large number of common genes were found to be expressed in reactive and nonreactive astrocytes (Fig. 3A, B; see also Beckervordersandforth et al, 2010; Cahoy et al, 2008; Zamanian et al, 2012; Zhang et al, 2014). Conversely, genes specific for neurons, microglia, or oligodendroglia were consistently very low, confirming the selective sorting of astrocytes (Fig.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…As expected, a large number of common genes were found to be expressed in reactive and nonreactive astrocytes (Fig. 3A, B; see also Beckervordersandforth et al, 2010; Cahoy et al, 2008; Zamanian et al, 2012; Zhang et al, 2014). Conversely, genes specific for neurons, microglia, or oligodendroglia were consistently very low, confirming the selective sorting of astrocytes (Fig.…”
Section: Resultssupporting
confidence: 77%
“…Conversely, genes specific for neurons, microglia, or oligodendroglia were consistently very low, confirming the selective sorting of astrocytes (Fig. 3B; see also Cahoy et al, 2008; Zhang et al, 2014). Notably, reactive astrocytes showed significantly lower expression of most astrocyte‐specific genes (selected as astrocyte‐specific from Cahoy et al 2008, Zhang et al 2014), except for Aldh1l1 and GFAP (Fig.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…In contrast to the mixed distribution of GPR37, GPR37L1 is highly expressed in astrocytes, with in situ hybridization revealing greatest density of GPR37L1 within the Bergmann glia of the cerebellum (Valdenaire et al, 1998). Microarray studies reported more than 100 times higher expression of GPR37L1 in rat and mice astrocytes compared with neurons (Cahoy et al, 2008; Lovatt et al, 2007; Zhang et al, 2014). GPR37L1 is also expressed in oligodendrocytes (Zhang et al, 2014).…”
Section: Potential Therapeutic Targets In Astrocytesmentioning
confidence: 99%